2013
DOI: 10.1371/journal.pone.0071409
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Fitness in Children and Young Adults with Primary Ciliary Dyskinesia

Abstract: BackgroundAlthough aerobic fitness is regarded as an overall prognostic measure of morbidity and mortality, its evaluation in the chronic progressive sinopulmonary disease primary ciliary dyskinesia (PCD) has been infrequently and inconsistently reported. Here we assessed peak oxygen uptake (VO2peak) in a large well-characterized cohort of PCD patients, and explored whether VO2peak was associated with parameters of pulmonary function, self-reported physical limitations, and physical activity level.MethodsVO2pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 52 publications
7
54
2
2
Order By: Relevance
“…118 Thus, airway clearance is expected to be quite beneficial in PCD and should be a cornerstone of long-term therapy. Daily cardiovascular exercise should also be strongly encouraged, as poor exercise capacity is linked to decreased pulmonary function in PCD, 119 and exercise may improve mucus clearance. 120 Antibiotics should be given for acute respiratory exacerbations in PCD.…”
Section: Routine Therapies In Pcdmentioning
confidence: 99%
“…118 Thus, airway clearance is expected to be quite beneficial in PCD and should be a cornerstone of long-term therapy. Daily cardiovascular exercise should also be strongly encouraged, as poor exercise capacity is linked to decreased pulmonary function in PCD, 119 and exercise may improve mucus clearance. 120 Antibiotics should be given for acute respiratory exacerbations in PCD.…”
Section: Routine Therapies In Pcdmentioning
confidence: 99%
“…Measures of global ventilation distribution inhomogeneity using the multiple‐breath inert gas washout (MBW) method provide important information that complements standard pulmonary function tests, such as spirometry, and are highly sensitive for detecting both early and established lung damage in cystic fibrosis (CF) and primary ciliary dyskinesia (PCD) . MBW requires minimal active patient cooperation and is feasible in all age groups; therefore, it may be appropriate as a future clinical tool for monitoring disease severity in these patients …”
Section: Introductionmentioning
confidence: 99%
“…The QOL-PCD scales correlated with a generic HRQoL measure PedsQL on scales assessing similar constructs. Convergent validity was also confirmed between scales of the QOL-PCD and generic versions measuring the same construct (CAT, SN-5, and SNOT-20 [35][36][37][38]40,41 Cystic Fibrosis Questionnaire, 40 Leicester Cough Questionnaire, 35 Sino-Nasal Outcome Test-22, 40 and Medical Outcomes Study Short Form-36. 38,39,41 These studies indicated that generic measures lack sensitivity to the specific concerns of patients with PCD; this could limit our assessment of convergent and divergent validity.…”
Section: Discussionmentioning
confidence: 70%
“…Comparison of QOL‐PCD with generic measures has limitations. This has been highlighted in a number of studies that have assessed HRQoL in patients with PCD by using generic measures, such as the St George Respiratory Questionnaire, Cystic Fibrosis Questionnaire, Leicester Cough Questionnaire, Sino‐Nasal Outcome Test‐22, and Medical Outcomes Study Short Form‐36 . These studies indicated that generic measures lack sensitivity to the specific concerns of patients with PCD; this could limit our assessment of convergent and divergent validity …”
Section: Discussionmentioning
confidence: 99%